The Influence of Obesity on Coagulation in Healthy Term Pregnancy as Assessed by Rotational Thromboelastometry. Issue 2 (24th June 2021) - Lee, J.; Eley, V.A.; Wyssusek, K.H.; Kimble, R.M.N.; Way, M.; Cohen, J.; van Zundert, A.A.
Abstract : ( Aust N Z J Obstet Gynaecol . 2020;60:714–719) Rotational thromboelastometry (ROTEM), a point-of-care coagulation test, has demonstrated hypercoagulability in both the pregnant and obese populations. This enhanced clotting tendency in pregnant patients can prove crucial in preventing postpartum hemorrhage. This study aimed to assess the combined effect of pregnancy and obesity on coagulation in healthy women using ROTEM.